Genotype of autosomal recessive congenital ichthyosis from a tertiary care center in India. Issue 3 (12th April 2022) - Chiramel, Minu Jose; Mathew, Lydia; Athirayath, Rekha; Chapla, Aaron; Sathishkumar, Dharshini; Mani, Thenmozhi; Danda, Sumita; George, Renu
Abstract: Background: Autosomal recessive congenital ichthyosis (ARCI) refers to non‐syndromic ichthyosis caused by mutations in one of the 13 identified genes. There are limited data on the genotype of ARCI and its phenotypic correlation from India. Objectives: The aim of this study was to characterize the genotype of ARCI among patients from the Indian subcontinent. Methods: Twenty‐eight patients clinically diagnosed as ARCI were recruited prospectively from September 2017 to June 2019 (21 months). DNA was extracted from peripheral blood and analyzed for the 13 described ARCI genes— TGM1, ABCA12, ALOX12B, ALOXE3, CERS3, CYP4F22, LIPN, NIPAL4, PNPLA1, SDR9C7, SLC27A4, SULT2B1, and CASP14 by next‐generation sequencing using an in‐house panel. The variants identified were confirmed by Sanger sequencing and compared with known pathogenic variants to establish pathogenicity. We also attempted to correlate the phenotype with the genotype. Results: Among the 28 patients recruited (M = 17, F = 11), we identified phenotypes of congenital ichthyosiform erythroderma in 12 (42.9%), 8 with lamellar ichthyosis (28.6%), 5 with intermediate phenotype (17.9%), and 3 with bathing suit ichthyosis (10.7%). Pathogenic and likely pathogenic variants were identified in 22 (78.6%) patients, involving 7 out of the 13 known ARCI genes while 6 (21.4%) did not have pathogenic variants. These included TGM1 mutation in 6 (21.4%), ALOX12B and ALOXE3 in 4 (14.3%) each, NIPAL4 and PNPLA1 in 3 (10.7%) each, and ABCA12 and CERS3 in 1 (3.6%) patient each. Previously unknown pathogenic variants were found in 59.1 % of patients. Conclusions: Our patients with ARCI were found to have genotypes as previously described in other populations.